2013
DOI: 10.1371/journal.pone.0071789
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible Electroporation of Human Primary Uveal Melanoma in Enucleated Eyes

Abstract: Uveal melanoma (UM) is the most common primary intraocular tumor in adults and is characterized by high rates of metastatic disease. Although brachytherapy is the most common globe-sparing treatment option for small- and medium-sized tumors, the treatment is associated with severe adverse reactions and does not lead to increased survival rates as compared to enucleation. The use of irreversible electroporation (IRE) for tumor ablation has potential advantages in the treatment of tumors in complex organs such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…Uveal melanoma (UM) is a common intraocular malignancy in adults, severely threatening their visual acuity, eyeball, even life (Mandel et al, 2013). It is reported that >50% of patients with UM eventually develop distant metastasis (Spagnolo, Caltabiano, & Queirolo, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Uveal melanoma (UM) is a common intraocular malignancy in adults, severely threatening their visual acuity, eyeball, even life (Mandel et al, 2013). It is reported that >50% of patients with UM eventually develop distant metastasis (Spagnolo, Caltabiano, & Queirolo, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It has furthermore been iterated that IRE had also been investigated within ex-vivo human eye models for the treatment of uveal melanoma [10,72], as well as in thyroid cancer [10,73].…”
Section: Other Organsmentioning
confidence: 99%
“…Moreover, cells may also die by apoptosis due to change in homeostasis. This phenomenon is called irreversible electroporation (IRE) 13 , 14 , which is used for bacterial inactivation 15 , tumor ablation 16 , 17 , and food processing 18 .…”
Section: Introductionmentioning
confidence: 99%